2013
DOI: 10.1007/s00221-013-3669-z
|View full text |Cite|
|
Sign up to set email alerts
|

Serotonergic modulation of suicidal behaviour: integrating preclinical data with clinical practice and psychotherapy

Abstract: with personality disorders), aiming to invite the reader to integrate some aspects of the neurobiology of human suicidal behaviour into a model of suicide that can be used in a clinical encounter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 223 publications
(209 reference statements)
0
1
0
Order By: Relevance
“…Several researches have also studied suicidal behaviour from a biological perspective (26,27). Despite the sustained emphasis on the role of (mainly serotonergic) neurotransmitter systems on suicidal behaviour (27)(28)(29), accumulating research has also suggested that immune/in ammatory and/or kynurenine pathway abnormalities may be a key to a biological substrate common to several types of mental suffering (or mental pain) and, therefore, could also be present in suicidal behaviours (30)(31)(32).…”
Section: Gender Perspectivementioning
confidence: 99%
“…Several researches have also studied suicidal behaviour from a biological perspective (26,27). Despite the sustained emphasis on the role of (mainly serotonergic) neurotransmitter systems on suicidal behaviour (27)(28)(29), accumulating research has also suggested that immune/in ammatory and/or kynurenine pathway abnormalities may be a key to a biological substrate common to several types of mental suffering (or mental pain) and, therefore, could also be present in suicidal behaviours (30)(31)(32).…”
Section: Gender Perspectivementioning
confidence: 99%